Economic Evaluation on the Production of Poly-DADMAC and Sepiolite Nanocomposite - Dita Ayu Rosmawati; Azzahra Annur Rizqia; Sifathul Jannah; Nissa Nur Azizah; Asep Bayu Dani Nandiyanto (International Journal of Research and Applied Technology (INJURATECH), 2021)
Some agricultural wastes are not suitable for direct disposal to standard sewage treatment plants and pre-treatment is required to avoid clogging by colloidal materials. One of the pre-treatment stages is coagulation and flocculation. In several studies, the mixture of polymer and clay fulfills the properties of coagulant and flocculant materials. A mixture of poly-DADMAC polymer and sepiolite clay can be used as a coagoflocculant at the same time. This study aims to analyze whether a project to manufacture clay polymer nanocomposites is feasible or not. By taking into account various perspectives including engineering and economic perspectives, this project is considered prospective to be carried out. This is indicated by the increase in the Profitability Index (PI) value of 5.33658 in the third year from -0.00975 which was the PI value the previous year. In twenty-four hours, the project can produce approximately 8.25 tonnes of adsorbent. The total profit earned in one year reaches 719,738.04 USD when run under ideal conditions. Apart from the results of the economic analysis mentioned, this project is also very effective in terms of time because it is simple and the raw materials needed are abundant